Identification of provincial-scale wildlife-vehicle collision hotspots involving white-tailed deer (Odocoileus virginianus), American black bear (Ursus americanus), and moose (Alces alces) in Nova Scotia, Canada - Pigden, Rachel (University of Guelph, 2024)
Wildlife-vehicle collisions (WVCs) are a widespread consequence of expansive road networks that have repercussions for wildlife movement and human safety; identifying WVC hotspots is a well-established method of locating areas for mitigation projects. This thesis identifies provincially important WVC hotspots for white-tailed deer (Odocoileus virginianus), American black bear (Ursus americanus), and moose (Alces alces) in Nova Scotia, Canada using Optimized Hotspot Analysis, a user-friendly tool that is here adapted to analyze a complex and extensive road network. Hotspots occurred in several notable areas including the Chignecto Isthmus (notably for black bear and moose), close to human settlement areas (white-tailed deer), and along major roads (all groups). An analysis of this kind has not previously been performed in Nova Scotia and this research provides valuable insights into the locations and severity of WVCs in the province using a unique methodological approach that can be adapted for use elsewhere. University of Guelph Ontario Graduate Scholarship